Theoretical study on the CaH6 system - Bagua, El Haouas; Khenchoul, Salah (Université Amar Telidji - Laghouat - Département des sciences de la matière, 2018)
The objective of this work is an ab initio calculation of the physicals properties: structural, electronic and Vibrational of CaH6, which is one of the new superconductors called clathrate calcium hydride at high pressures. The calculation was conducted in the framework of the functional theory of density (DFT), and it have been performed with the ABINIT open source software, using the potential exchange-correlation GGA parameterized by Perdew, Burke and Enzerhof (PBE). By applying the density-functional perturbation theory (DFPT), one can also study the response of a solid to disturbances like electric fields or the displacement atoms. The results obtained were commented and compared with the available experimental data.